Indian herbal remedies for diabetes as a cause of lead poisoning. - Keen, R. W. (BMJ Group, 1994)
Herbal remedies from the Indian subcontinent have been found to have high concentrations of heavy metals and unsupervised treatment may result in toxicity. We report the case of an Indian patient with hepatitis who was found to have lead poisoning where the source was traced to ethnic remedies he had been taking for diabetes.